2019
DOI: 10.3390/biom10010012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acids and Microbiota-Brain Communication in Neuropsychiatric Diseases

Abstract: The gut-brain axis is a multimodal communication system along which immune, metabolic, autonomic, endocrine and enteric nervous signals can shape host physiology and determine liability, development and progression of a vast number of human diseases. Here, we broadly discussed the current knowledge about the either beneficial or deleterious impact of dietary fatty acids on microbiota-brain communication (MBC), and the multiple mechanisms by which different types of lipids can modify gut microbial ecosystem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 257 publications
(314 reference statements)
0
27
0
1
Order By: Relevance
“…They also interfere with cytokine gene expression. As monocytes are the main effector cells of the immune system, long-chain n-3 PUFA influence monocyte/macrophage defensive functions; both EPA and DHA can enhance phagocytic activity and decline chemotaxis of monocytes in humans (40).…”
Section: Mechanism Of Immunomodulationmentioning
confidence: 99%
“…They also interfere with cytokine gene expression. As monocytes are the main effector cells of the immune system, long-chain n-3 PUFA influence monocyte/macrophage defensive functions; both EPA and DHA can enhance phagocytic activity and decline chemotaxis of monocytes in humans (40).…”
Section: Mechanism Of Immunomodulationmentioning
confidence: 99%
“…It plays many specific functions, including maintenance of structural integrity of the gut mucosal barrier [ 9 ], development of the immune system [ 20 ], protection against enteric pathogens [ 21 ] and production of several nutrient-derived metabolites with potential to affect human metabolic function [ 22 ]. For these reasons, the alteration of microbial composition (known as dysbiosis) may lead to a pro-inflammatory state and the development of many pathologies including, gastrointestinal illnesses, metabolic diseases and brain disorders [ 23 , 24 , 25 , 26 ]. Recently, the connection between the brain and gut, the so-called gut–brain axis, has been involved in regulating feeding and appetite, glucose homeostasis and gut motility [ 27 ].…”
Section: Microbiota Immunity and Inflammationmentioning
confidence: 99%
“…Although, microbiota composition can be influenced by numerous external factors, several studies have demonstrated the strong influence of diet and dietary patterns on the structure and function of GM and their effect on health [ 58 ]. For instance, it has been shown that different dietary fatty acids may impact on the microbiota–brain communication to significantly affect the pathophysiology of neuropsychiatric diseases [ 23 ]. Likewise, unbalanced diets (mainly Western diets) may induce dysbiosis resulting in increased gut permeability and low-grade inflammation.…”
Section: Microbiota Immunity and Inflammationmentioning
confidence: 99%
“…The gut-brain axis is a multimodal communication system that is connected by both sympathetic and parasympathetic nervous systems, together with hormones that circulate as well as other molecules that regulate the nervous system (Mayer, 2011;Marrone & R, 2019). Recent studies have shown that the function of the gut-brain axis involves intestinal flora and plays a major role in brain and gut communication.…”
Section: Introductionmentioning
confidence: 99%